THE EFFECT OF DIGITAL PAYMENT, PEER-TO-PEER (P2P) LENDING, AND MARKETPLACE ON THE DEVELOPMENT OF SMEs DURING A PANDEMIC - Ramadhini Wahyuningrum; Indrawati Yuhertiana (Jambura Economic Education Journal, 2023)
This study aims to examine the influence of Digital Payments, Peer To Peer (P2P) Lending, and Marketplace on the development of micro, small, and medium enterprises (MSMEs) during the Surabaya City pandemic. This type of research approach uses a quantitative approach. The sampling technique used purposive sampling and data analysis using Partial Least Square (PLS) with a test tool in the form of SmartPLS 3. The data source is primary data obtained from the results of distributing questionnaires, namely MSME actors in Surabaya as many as 86 respondents. The results of this study indicate that (1) Digital payments have no effect on the development of MSMEs during the pandemic (2) Peer-to-Peer Lending has an effect on the development of MSMEs during the pandemic (3) Marketplace affects the development of MSMEs during the pandemic.